Validation of the MOS-HIV as a Measure of Health-Related Quality of Life in Persons Living with HIV and Liver Disease - Henderson, Wendy A. (2010)
BACKGROUND: Management of HIV infection with potent antiretroviral medication has transformed HIV into a chronic condition and has shifted much of the burden of disease to co-morbid conditions such as liver disease. Liver disease (LD) alone has been shown to have a significant effect on one’s health-related quality of life (HRQOL). Clinical evidence suggests that the growing number of persons living with HIV+LD may have a poorer HRQOL than persons with HIV without LD. To date, the widely accepted instrument to assess HRQOL, HIV Medical Outcomes Survey (MOS-HIV), has not been evaluated for reliability and validity in a population of HIV infected persons with LD. METHODS: HRQOL was prospectively assessed using the MOS-HIV in a sample of 532 HIV-infected adults on antiretroviral therapy (n=305 HIV and n=227 HIV+LD). In addition, participants completed standardized questionnaires of sociodemographics and co-morbid conditions. RESULTS: The psychometric properties of the HIV Medical Outcomes Survey were supported by testing reliability and construct, convergent, discriminative, and predictive validity. The MOS-HIV discriminated between those persons living with HIV with and without LD on the basis of the physical function subscale scores (p=.018). CONCLUSION: This study found the MOS-HIV valid and reliable instrument in persons with HIV+LD.